A new approach to compatibilization study of EVA/PMMA polymer blend used as an optical fibers adhesive: Mechanical, morphological and thermal properties. (March 2018) - Tomić, Nataša Z.; Marinković, Aleksandar D.; Veljović, Đorđe; Trifković, Kata; Lević, Steva; Radojević, Vesna; Jančić Heinemann, Radmila
Abstract: Mechanical, morphological and thermal properties of optical fiber adhesives, based on poly(ethylene- co -vinyl acetate) (EVA) with 18 and 40% of vinyl acetate, polymer blend of EVA/poly(methyl methacrylate) (PMMA), and graft polymer, raw EVA- g -PMMA, prepared via in situ free radical polymerization, were studied. Extraction of PMMA homopolymer from raw EVA- g -PMMA produced purified EVA- g -PMMA, which enable quantitative determination of graft initiating centers by NMR spectroscopy. FTIR and image analysis allowed determination of the graft content/level in purified EVA- g -PMMA. Grafting effect to compatibilization efficiency in EVA- g -PMMA was monitored by image analysis of gelation processes and determination of wetting angle. Single lap joint of adhesives/optical fibers were subjected to adhesive testing before and after aging on 60 °C for 60 h and 120 h. Thermogravimetry coupled with mass spectrometry showed different thermal stability and degradation pathways of adhesives, and reduced the degree of deacetylation of thermally treated EVA- g -PMMA adhesive. DSC analysis showed higher thermal stability of EVA- g -PMMA adhesive. Better mechanical properties of EVA- g -PMMA, i.e . 62.4% higher Charpy impact strength value in relation to EVA, was obtained.